2014
DOI: 10.1073/pnas.1409572111
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying selection in immune receptor repertoires

Abstract: The efficient recognition of pathogens by the adaptive immune system relies on the diversity of receptors displayed at the surface of immune cells. T-cell receptor diversity results from an initial random DNA editing process, called VDJ recombination, followed by functional selection of cells according to the interaction of their surface receptors with self and foreign antigenic peptides. Using high-throughput sequence data from the β-chain of human T-cell receptors, we infer factors that quantify the overall … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
162
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 147 publications
(190 citation statements)
references
References 25 publications
27
162
1
Order By: Relevance
“…This effect is reproduced in detail by the model calculations. This result generalizes previous observations that the number of shared TCRs between a pair of individuals should scale approximately with the product of the numbers of unique TCRs in each sample20, 21, 26, 43 to arbitrary sharing numbers.…”
Section: From Samples To Full Repertoiressupporting
confidence: 88%
See 4 more Smart Citations
“…This effect is reproduced in detail by the model calculations. This result generalizes previous observations that the number of shared TCRs between a pair of individuals should scale approximately with the product of the numbers of unique TCRs in each sample20, 21, 26, 43 to arbitrary sharing numbers.…”
Section: From Samples To Full Repertoiressupporting
confidence: 88%
“…We have found that an overall selection factor is needed to predict sharing numbers correctly, but this simple and effective model is sequence independent. Previous work20 inferred a sequence‐specific selection process by comparing generation model results to observed sequences. In principle, such a model could be combined within our framework to yield refined sharing predictions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations